Sympathetic and renin-angiotensin-aldosterone system activation in heart failure with preserved, mid-range and reduced ejection fraction. (1st December 2019) - Vergaro, Giuseppe; Aimo, Alberto; Prontera, Concetta; Ghionzoli, Nicolò; Arzilli, Chiara; Zyw, Luc; Taddei, Claudia; Gabutti, Alessandra; Poletti, Roberta; Giannoni, Alberto; Mammini, Chiara; Spini, Valentina; et al.
Abstract: Background: Evidence of sympathetic and renin-angiotensin-aldosterone system activation provided a rationale for neurohormonal antagonism in heart failure with reduced ejection fraction (HFrEF), while no data are available in patients with milder degree of systolic dysfunction. We aimed to investigate neurohormonal function in HF with preserved and mid-range EF (HFpEF/HFmrEF). Methods: Three cohorts (n = 189/each) of stable HFpEF, HFmrEF and HFrEF patients were selected (median age 70, 67 and 67 years; male 56%, 73% and 74%, respectively). Patients received a baseline clinical assessment including plasma renin activity (PRA), aldosterone, catecholamines, and N-terminal fraction of pro-B-type natriuretic peptide (NT-proBNP) assays, and were followed-up for all-cause death. Results: Neuroendocrine profile was similar between HFpEF and HFmrEF, while all neurohormones except epinephrine were higher in HFrEF than in HFmrEF (NT-proBNP 2332 ng/L, IQR 995–5666 vs 575 ng/L, 205–1714; PRA 1.7 ng/mL/h, 0.4–5.6 vs 0.6 ng/mL/h, 0.2–2.6; aldosterone 153 ng/L, 85–246 vs 113 ng/L, 72–177; norepinephrine 517 ng/L, 343–844 vs 430 ng/L, 259–624; all p < 0.001, epinephrine 31 ng/L, 10–63 vs 25 ng/L, 10–44; p = 0.319). These findings were unrelated to treatment heterogeneity. Ten percent of HFpEF patients had elevated PRA, aldosterone and norepinephrine vs. 8% in HFmrEF and 21% in HFrEF. During a 5-year follow-up, survival decreased with the number of neurohormones elevated (HFpEF: log-rank 7.8, p = 0.048; HFmrEF: log-rank 11.8, p = 0.008; HFrEF: log-rank 8.1, p = 0.044). Conclusions: Neurohormonal activation is present only in a subset of patients with HFpEF and HFmrEF, and may hold clinical significance. Neurohormonal antagonism may be useful in selected HFpEF/HFmrEF population. Highlights: Neurohormonal activation has been well documented in HFrEF. There is limited evidence on neurohormonal activation in HFpEF and HFmrEF. Sympathetic and RAAS activation is present only in a group of HFpEF/HFmrEF patients. Neurohormonal blockade may be useful only in a subset of HFpEF/HFmrEF patients.